Comparison of wearable sensor to traditional methods in functional outcome measures: A systematic review. Issue 10 (20th December 2020) - Follis, Shawna; Chen, Zhao; Mishra, Sachin; Howe, Carol L.; Toosizadeh, Nima; Dohm, Michael
Abstract: Traditional methods of collecting functional outcome measures are widely used for lower extremity arthroplasty outcome assessment. Wearable sensors are emerging as viable tools for functional outcome measures in monitoring of postarthroplasty recovery. The objective of this review was to compare the efficacy of wearable sensors with traditional methods for monitoring postarthroplasty functional recovery. Articles were searched for inclusion in this review that used both traditional and wearable sensor functional outcome measures to assess lower extremity function before and after lower extremity arthroplasty. Two independent screeners reviewed all articles, and resolved differences through consensus and consultation with the senior author. Studies that met inclusion criteria were evaluated for methodologic quality using performed risk of bias assessments. Results from several traditional and wearable sensor functional outcome measures from baseline through follow‐up were normalized across studies. Fourteen articles met the inclusion criteria. Six studies used statistical methods to directly compare functional outcome measures and eight studies used qualitative description of comparisons. This review found evidence that wearable sensors detected nuanced functional outcome information on the specific biomechanics and timing of recovery, which were unaccounted for using traditional methods. Wearable sensors have shown promising utility in providing additional recovery information from lower extremity arthroplasty compared with traditional functional outcome measures, but future research is needed to assess the clinical significance of this additional information. Wearable sensor technology is an emerging clinical tool providing advanced and determinative data with the potential for advancing the assessment of lower extremity arthroplasty outcomes.